Oncolytic Adenovirus—A Nova for Gene-Targeted Oncolytic Viral Therapy in HCC - Abudoureyimu, Mubalake; Lai, Yongting; Tian, Chuan; Wang, Ting; Wang, Rui; Chu, Xiaoyuan (Frontiers in Oncology, 2019)
Hepatocellular carcinoma (HCC) is one of the most frequent cancers worldwide, particularly in China. Despite the development of HCC treatment strategies that the survival rate remains unpleasant. Gene-targeted oncolytic viral therapy “GTOVT” is an emerging treatment modality that a kind of cancer targeted therapy which accomplishes viral vectors armed with anti-cancer genes. Adenovirus is a promising agent for GAOVT due to an abundance of advantages. In spite of oncolytic adenovirus itself, the host immune response is the determining factor for the anti-cancer efficacy. In this review, we had summarized recent developments in oncolytic adenovirus engineering and the novel therapeutic genes utilized in HCC treatment. Furthermore, the diversified roles of immune response play in oncolytic adenovirus therapy and recent attempts to modulate immune responses to enhance the anti-cancer efficacy of oncolytic adenovirus have been discussed.